Population Structure and Implications on the Genetic Architecture of HIV-1 Phenotypes Within Southern Africa - Thami, Prisca K.; Chimusa, Emile R. (Frontiers in Genetics, 2019)
The interesting history of Southern Africa has put the region in the spotlight for population medical genetics. Major events including the Bantu expansion and European colonialism have imprinted unique genetic signatures within autochthonous populations of Southern Africa, this resulting in differential allele frequencies across the region. This genetic structure has potential implications on susceptibility and resistance to infectious diseases such as human immunodeficiency virus (HIV) infection. Southern Africa is the worst affected region by HIV. Here, we discuss advances made in genome-wide association studies (GWAS) of HIV-1 in the past twelve years and dissert population diversity within Southern Africa. Our findings accentuate that a plethora of factors such as migration, language and culture, admixture and natural selection have profiled the genetics of the people of Southern Africa. Genetic structure has been observed among the Khoe-San, among Bantu-speakers, and between the Khoe-San, Coloureds and Bantu-speakers. Moreover, Southern African populations have complex admixture scenarios. Few GWAS of HIV-1 have been conducted in Southern Africa, with only one of these identifying two novel variants (HCG22 rs2535307 and CCNG1 kgp22385164) significantly associated with HIV-1 acquisition and progression. High genetic diversity, multi-wave genetic mixture and low linkage disequilibrium of Southern African populations constitute a challenge in identifying genetic variants with modest risk or protective effect against HIV-1. We therefore posit that it is compelling to assess genome-wide contribution of ancestry to HIV-1 infection. We further suggest robust methods that can pin-point population specific variants that may contribute to the control of HIV-1 in Southern Africa.